The fabrication of the complex bio-fertilizer for wheat cultivation based on collection bacteria of the PGPR group - RAKHILYA AIPOVA; AIZHAN ABDYKADYROVA; DMITRY SILAYEV; ERKIN TAZABEKOVA; IRINA OSHERGINA; EVGENIY TEN; ASKAR KURMANBAYEV (Society for Indonesian Biodiversity, 2020)
Abstract. Aipova R, Abdykadyrova A, Silayev D, Tazabekova E, Oshergina I, Ten E, Kurmanbaye A. 2020. The fabrication of the complex bio-fertilizer for wheat cultivation based on collection bacteria of the PGPR group. Biodiversitas 21: 5021-5028. The development of new types of biological products based on microbial complexes from local bacterial strains is a great theoretical and practical interest for agriculture. It can provide an opportunity for better preservation of the natural properties of the wheat products under extreme conditions. The aim of this study was to obtain and test a biological product to increase wheat productivity in northern Kazakhstan. Our data indicate the potential of Plant Growth-Promoting Rhizobacteria (PGPR) group bacteria for the development of biofertilizers and biopesticides. For instance, the bacteria B. mojavensis showed effectiveness in the experiments with the wheat (Astana-2 type). We observed an increase in wheat yield by 15% under conditions of artificial infection of crops with snow mold (by 2.5fold compared with the control). The results demonstrated that the B. mojavensis Lhv 97 strain can be used as an ingredient of biological products due to its activity against plant diseases caused by phytopathogenic fungi.